Desenvolvimento e otimização de materiais nanocristalinos para células solares sensibilizadas - Trino, Luciana Daniele [UNESP] (2014)
Considering the rising demand for electricity and the environmental changes caused by the use of non-renewable energy sources, solar energy is presented as a good alternative to fossil fuels. Among the photovoltaic devides, dye sensitized solar cells (DSSC'S) use abundant in nature and low cost materials. Nevertheless, is necessary to improve the DSSC's by increasing their efficiency and making them marketable. To obtain a good efficiency in the device, it is also essential to control the structural and optical properties of the semiconductors employed. In these devices, the titanium dioxide is used as a semiconductor presenting a wide band-gap which absorbs light at wavelengths capable of genertaing electron-hole pairs. Zinc oxide is applied as a transparent conductor oxide which has high optical transmittance. Thin films of TiO2 and ZnO were synthesized by sol-gel route and deposited by spin-coating technique on glassy substrate in order to study the deposition conditions and investigate their structural and optical properties. The specimes were characterized by X-ray diffraction, scanning electron microscopy, confocal optical microscopy, atomic force microscopy and spectroscopyin the UV-Vis. Structural analysis showed that the surfactant concentration, the parameters of the film deposition and the heat treament temperatures employed had a major influence on the adhesion of the films at the glassy substrate, on the crystal phase formed, on the particle size and on the homegeneity of the film surface. The optical studies of ZnO showed a band gap value consistent with the literature (3.3 eV) and transmittance above 80%. TiO2 films exchibited absorption around 400 nm a high gap for the anatase crystalline phase of 4.1 eV, due to the presence of brookite phase. TiO2-ZnO films presented the same values for TiO2 films of 4.1 eV